Unlawful for Other Than Regular Militia to Drill, Ch. 1525, § 1, in Acts of the General Assembly of the Commonwealth of Kentucky (1888). - (:unkn) unknown (General Publisher, 1888)
It shall be unlawful for any body of men whatever, other than the regular organized militia of this Commonwealth, and the troops of the United States, to associate themselves together as a military company or other armed organization
--
Keywords: MILITIAS